A new Peruvian species of Megarthrus Curtis (Coleoptera: Staphylinidae: Proteininae) - Pérez, Luis; Rodríguez, Maryzender; Asenjo, Angélico (Zootaxa, 2020)
A new species of Megarthrus Curtis is described from the Eastern slopes of the Andes in southeastern Peru (Department of Cuzco). Major diagnostic features are photographed and illustrated, and COI molecular barcode is given.